Emotional eating, snacking behavior and nutritional status among adolescents - Yulia Rachmawati; Sapja Anantanyu; Kusnandar Kusnandar (International Journal of Public Health Science (IJPHS), 2019)
The tendency to eat in response to stress known as emotional eating (EmE). Individuals with EmE usually has been change their dietary pattern towards more unhealthy snacking which contribute to overweight. This study aims to examine the interrelationship between EmE, snacking behavior and nutritional status among adolescents. This was an analytic observational with a cross sectional design study. It was conducted in Surakarta, on August 2019. Total 140 adolescents aged 14-17 years were selected. The data ofEmE were measured by Emotional Eater Questionnaire (EEQ), data of snacking behaviour measured by food frequencies questionnaire (FFQ),and BMI were measured using weight scale and microtoice. Data wereanalyzed by descriptive, bivariate and binary logistic using SPSS v.23. There was significantly difference of EmE and snacking behavior in underweight, normal, and overweight adolescents. We found that underweight (4.17±3.16) and normal individuals (4.97±4.19) were not an emotional eater, and less sweet snacks and sweet drinks consumption while overweight individuals were an emotional eater (14.26±6.04) and eat more sweet snacks, and sweet drinks (p<0.001) during negative emotional states. It was shown that emotional eating and snacking behavior were found higher in overweight than underweight and normal individuals.